Metode Belajar Kelompok dengan Tutor Sebaya dalam Meningkatkan Aktivitas dan Hasil Belajar Siswa Hindu di SMPN 1 Basarang Kabupaten Kapuas - I Komang Mertayasa (Bawi Ayah: Jurnal Pendidikan Agama dan Budaya Hindu, 2022)
The use of learning methods that are less varried students saturation in learning. This has an impact on the acquisition of unsatisfactory students learning outcomes, Therefor the application of vafious learning methods need to be applied. Learning Hindu religious education at SMPN 1 Basarang still uses conventional methods so that students become less active and the minimun completeness criteria have not fully achieved by students. One solution that can be applied by teachers is to improve learning through the application of peer tutor learning methods. After conducting classroom action research with peer tutor learning methods, the results showed that there was an increase in learning outcomes and student activities in learning Hindu religious education. This can be seen from the final test of the first cycle, namely students who completed as many as 10 students from 18 students who took the test with the percentage of students' classical learning mastery scores reaching 55.56%, and classical absorption reaching 67.83%. While in the second cycle there was an increase, from 18 students who took the test only two students who did not meet individual absorption with classical learning mastery of 84.67% and classical absorption of 83.33%. In the first cycle the student's activity reached 74.38%, while in the second cycle the student's activity increased to 97.50%.